Elementary biophysics : an introduction - Srivastava, P. K. (Pradeep K.) (Harrow, U.K. : Alpha Science International, 2005)
This book was developed to explain the elementary principles of physics to biology students and later expanded to include descriptions of the structure and functions of cells and their components and other biosystems for physics students.
What is biophysics? -- Part A: Systemic biophysics -- Biomechanics -- Biophysics and fluid flow -- Biophysics and gas transport -- Physics of audition -- Physics of vision -- Part B: Cellular-molecular biophysics -- Cell: its organelles and molecules -- Physics of biomolecules -- Physics of bio-membranes -- Thermodynamics and bio-systems -- Bioenergetics -- Neurobiophysics.
Includes index.
Keywords: Biophysics; Biophysics